PENGARUH FAKTOR PERILAKU KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN ASURANSI JIWA (STUDI PADA PT. ASURANSI JIWA SYARIAH BUMIPUTERA CABANG BANDA ACEH) - Israk Ahmadsyah; Isnaliana Isnaliana; Wediansyah Wediansyah (Program Studi Ekonomi Islam, Fakultas Ekonomi dan Bisnis - Universitas Syiah Kuala, 2021)
This study aims to determine the effect of Consumer Behavior Factors Against Life Insurance Purchasing Decisions (Study at PT. Asuransi Jiwa Syariah Bumiputera Banda Aceh Branch). Consumer behavior is very closely related to the problem of decisions taken by someone in competition and the determination to obtain and use goods and services. Consumers take many kinds of considerations to make purchasing decisions. This research is quantitative research. The population in this study is consumer behavior at PT. Sharia Life Insurance Bumiputera Banda Aceh Branch and a sample of 65 customers. The results of this study indicate that consumer behavior significantly influences the decision to purchase Bumiputera Sharia Life Insurance, Banda Aceh Branch (p-value=0.00, β=0.229).